2011
DOI: 10.1136/thx.2010.153825
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar CD4+ T cell responses to respiratory antigens are impaired in HIV-infected adults

Abstract: RationaleHIV-infected adults are at an increased risk of lower respiratory tract infections. HIV infection impairs systemic acquired immunity, but there is limited information in humans on HIV-related cell-mediated immune defects in the lung.ObjectiveTo investigate antigen-specific CD4+ T cell responses to influenza virus, Streptococcus pneumoniae and Mycobacterium tuberculosis antigens in bronchoalveolar lavage (BAL) and peripheral blood between HIV-infected individuals and HIV-uninfected Malawian adults.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 29 publications
5
80
2
3
Order By: Relevance
“…However, given the invasive nature and the associated risk of bronchoscopy, especially in HIV-infected persons, a longitudinal study was judged not to be justifiable. Furthermore, the alveolar lymphocyte counts from HIV-uninfected individuals were higher than has been reported previously (4,5,40). Household indoor air pollution is highly prevalent in Malawi (41) and it is possible that this group of individuals had ongoing alveolar inflammation.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…However, given the invasive nature and the associated risk of bronchoscopy, especially in HIV-infected persons, a longitudinal study was judged not to be justifiable. Furthermore, the alveolar lymphocyte counts from HIV-uninfected individuals were higher than has been reported previously (4,5,40). Household indoor air pollution is highly prevalent in Malawi (41) and it is possible that this group of individuals had ongoing alveolar inflammation.…”
Section: Discussioncontrasting
confidence: 43%
“…In high transmission regions, most TB cases in HIV-individuals result from recent Mycobacterium tuberculosis (Mtb) infection indicating that in these individuals the lung is more permissive for the establishment or progression of primary infections (3). Recent studies have reported that alveolar macrophage (AM) proteolytic function and mycobacterial antigen-specific Th1 CD4 1 T-cell responses in the lung are impaired in asymptomatic HIV-infected, antiretroviral therapy (ART)-naive persons (4)(5)(6). These findings indicate that HIV alters both innate and adaptive immunity in the lung to render HIV-infected individuals incapable of mounting adequate pulmonary immune responses to control Mtb.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…4 Kemampuan mikroorganisme menginfeksi paru-paru tidak hanya bergantung pada suatu patogenisitasnya, tetapi juga pada kemampuan mikroorganisme untuk mengatasi kekebalan tubuh tuan rumah. Infeksi HIV mengakibatkan penurunan kuantitatif dan juga kualitatif cluster of differentiation 4 (CD4) limfosit T. 5 Delapan puluh persen kasus pneumonia bakteri terjadi pada kondisi CD4 <400 sel/mm 3 dan pneumonia bakteri terbanyak terjadi pada CD4 <200 sel/ mm 3 . 6 Jenis bakteri gram positif yang menyebabkan infeksi paru tersering pada populasi HIV adalah Streptococcus pneumoniae (S. pneumoniae).…”
Section: Pendahuluanunclassified
“…Adult humans without ongoing infections have tremendous numbers of T cells residing in their lungs, equivalent to the total numbers in the blood (42). T cells in the lungs, nasal tissues, and blood of adults without ongoing infections respond to respiratory pathogens, such as pneumococcus and influenza, with greater responsiveness by T cells from the relevant tissues, suggesting a mucosal compartmentalization of immunity (42)(43)(44)(45). Respiratory pathogen-reactive T cells often generate IL-17 on stimulation (42,45), consistent with an ability to amplify neutrophil-mediated host defense in the lungs.…”
Section: Immune Remodeling and Secondary Responses In The Lungmentioning
confidence: 99%